2017
DOI: 10.1007/s00405-017-4647-z
|View full text |Cite
|
Sign up to set email alerts
|

Safety of flexible endoscopic biopsy of the pharynx and larynx under topical anesthesia

Abstract: Recent advancements in transnasal endoscopy enable a shift in diagnostic workup of lesions in the pharynx and larynx, from an examination with biopsy under general anesthesia to an office-based examination with flexible endoscopic biopsy under topical anesthesia. Procedural complications were evaluated to assess the safety of office-based flexible endoscopic biopsy in patients with benign and malignant laryngopharyngeal lesions. Patients who underwent flexible endoscopic biopsy from 2012 to 2016 were evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 16 publications
1
29
0
Order By: Relevance
“…OBB is well tolerated and safe. [16][17][18][19][20][21] Studies have shown that when the histological outcome of OBB has been invasive squamous cell carcinoma, the diagnosis has been confirmed in 100% of the cases with a final histological diagnosis using operative biopsies. [21][22][23] Median specialist-to-diagnosis and specialist-to-treatment intervals were significantly decreased from 9 to 2 days and from 34 to 21 days, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…OBB is well tolerated and safe. [16][17][18][19][20][21] Studies have shown that when the histological outcome of OBB has been invasive squamous cell carcinoma, the diagnosis has been confirmed in 100% of the cases with a final histological diagnosis using operative biopsies. [21][22][23] Median specialist-to-diagnosis and specialist-to-treatment intervals were significantly decreased from 9 to 2 days and from 34 to 21 days, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Office‐based laryngeal procedures in general have shown to be feasible, safe, and well tolerated by patients. They result in decreased time intervals to diagnosis and treatment and also reduce healthcare costs . In patients with benign laryngeal pathology and a contraindication for general anesthesia or with a lesion inaccessible by rigid endoscopy (e.g., patients with limited neck extension or dental limitations), office‐based CO 2 laser surgery is a minimally invasive therapeutic alternative.…”
Section: Discussionmentioning
confidence: 99%
“…Reasons for undergoing an office‐based procedure were either contraindications for general anesthesia, previously failed therapeutic laryngoscopy under general anesthesia, or a strong preference for a procedure under topical anesthesia by the patient. Patients underwent flexible endoscopic biopsy (FEB) under topical anesthesia to obtain histology prior to office‐based laser surgery according to our department's protocol . An exception was if patients with a medical history of a benign laryngeal tumor (e.g., laryngeal papilloma) were seen with suspicion of recurrent disease during flexible laryngoscopy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Our study showed very few postprocedural complications in both approaches as well as good tolerance of patients which agrees with other studies. 4,6,15 However, Shah and Johns reported that the transoral approach can be difficult to perform and is not well tolerated by some patients. On the other hand, transnasal access is generally better tolerated by most patients.…”
Section: Pre-and Postprocedures Precautionsmentioning
confidence: 99%